(X^2 -2x-5)^2 - 2 (x^2 - 2x-5)=3

(X^2 -2x-5)^2 - 2 (x^2 - 2x-5)=3
Гость
Ответ(ы) на вопрос:
Гость
[latex](x^2 -2x-5)^2 - 2 (x^2 - 2x-5)=3[/latex] Замена: [latex]x^2 -2x-5=t[/latex] [latex]t^2 - 2t-3=0[/latex] [latex]D=(-2)^2-4*1*(-3)=4+12=16[/latex] [latex]t_1= \frac{2+4}{2} =3[/latex] [latex]t_2= \frac{2-4}{2} =-1[/latex] [latex]x^2 -2x-5=3[/latex]                      или        [latex]x^2 -2x-5=-1[/latex] [latex]x^2 -2x-8=0[/latex]                      или         [latex]x^2 -2x-4=0[/latex] [latex]D=(-2)^2+32=36[/latex]             или         [latex]D=(-2)^2+16=20[/latex] [latex]x_1= \frac{2+6}{2}=4 [/latex]                         или        [latex]x'_1= \frac{2+2 \sqrt{5} }{2}=1+ \sqrt{5} [/latex] [latex]x_2= \frac{2-6 }{2}=-2[/latex]                      или       [latex]x'_2= \frac{2-2 \sqrt{5} }{2}=1- \sqrt{5} [/latex] Ответ: [latex]-2;[/latex] [latex]4;[/latex]  [latex]1б \sqrt{5} [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы